Case Report: Complete Response to Nivolumab in a Patient With Programmed Cell Death 1 Ligand 1-Positive and Multiple Gene-Driven Anaplastic Lymphoma Kinase Tyrosine Kinase Inhibitor-Resistant Lung Adenocarcinoma - Wen Dong (Frontiers Media S.A., 2021)
Multiple gene-driven programmed cell death 1 ligand 1 (PD-L1)-expressing non-small-cell lung cancer (NSCLC) is very rare. Previous studies have shown that patients with NSCLC with anaplastic lymphoma kinase (ALK) gene rearrangement rarely benefit from PD-L1 inhibitors. Besides the secondary mutations in ALK gene, other mechanisms might contribute to tumor resistance to ALK tyrosine kinase inhibitors (ALK-TKIs). Herein, we present a case of PD-L1-overexpressing lung adenocarcinoma that harbors both EML4-ALK gene rearrangement and BRAF mutation. In particular, a second molecular analysis after resistance to first- and second-generation ALK-TKIs revealed a high PD-L1 expression and tumor mutation burden. Therefore, treatment with nivolumab monotherapy, an anti-PD-1 inhibitor, was started and the patient achieved complete remission. This case report suggested that PD-1 inhibitors might be an effective treatment option for patients with multiple gene-driven PD-L1-expressing NSCLC harboring ALK gene rearrangement.